2011
DOI: 10.1096/fj.11-182519
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid dose determines osteocyte cell fate

Abstract: In response to cellular insult, several pathways can be activated, including necrosis, apoptosis, and autophagy. Because glucocorticoids (GCs) have been shown to induce both osteocyte apoptosis and autophagy, we sought to determine whether osteocyte cell fate in the presence of GCs was dose dependent by performing in vivo and in vitro studies. Male Swiss-Webster mice were treated with slow-release prednisolone pellets at 1.4, 2.8, and 5.6 mg/kg/d for 28 d. An osteocyte cell line, MLO-Y4 cells, was treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
111
2
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(128 citation statements)
references
References 80 publications
(105 reference statements)
9
111
2
6
Order By: Relevance
“…61 Low-dose glucocorticoid treatment has also been shown to induce autophagy in osteocytes in response to increased oxidative stress caused by treatment, preserving the viability of these cells. [62][63][64] Studies indicate that autophagy also plays an important role in bone resorption by osteoclasts. 65 It has been reported that proteins involved in the autophagic pathway are important in the regulation of osteoclastogenesis, 66,67 indicating that this process participates both in bone formation and resorption.…”
Section: Role Of Autophagy In Bone Biologymentioning
confidence: 99%
“…61 Low-dose glucocorticoid treatment has also been shown to induce autophagy in osteocytes in response to increased oxidative stress caused by treatment, preserving the viability of these cells. [62][63][64] Studies indicate that autophagy also plays an important role in bone resorption by osteoclasts. 65 It has been reported that proteins involved in the autophagic pathway are important in the regulation of osteoclastogenesis, 66,67 indicating that this process participates both in bone formation and resorption.…”
Section: Role Of Autophagy In Bone Biologymentioning
confidence: 99%
“…146,147 The specific depletion of BECN1 notably reduces both the size and formation efficiency of mammospheres, thus development of autophagy, preserving osteocyte viability depending on glucocorticoid dose. 129,130 Osteoblasts are the precursor of osteocytes and are responsible for bone formation. As osteoblasts actively produce mineralized matrix during bone formation, it is conceivable that autophagy is activated to meet the high-energy demands of active osteoblasts.…”
Section: Autophagy and Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Administration of GCs leads to a reduction in bone mineral density (BMD), decreased generation of osteoblasts and osteocytes and prolonged lifespan of osteoclasts, with fractures occurring in 30-50% of patients chronically treated with GCs (1). Recent studies have demonstrated that GCs can induce apoptosis and autophagy in osteocytes (4)(5)(6). The influence of GCs has been rarely reported on chondrocytes, which play a key role in skeletal development.…”
Section: Introductionmentioning
confidence: 99%